고지방식이 C57BL/6N 모델에서 降脂丸의 농도별 비알콜성 지방간질환 개선효과 - 안예지; Ye Ji Ahn; 윤기현; Ki Hyeon Yoon; 조주흠; Ju Heum Jo; 장두현; Du Hyon Jang; 정양삼; Yang Sam Jung; 김종훈; Jong Hoon Kim; et al. (대한본초학회지(본초분과학회지), 2014)
Objectives : This study was undertaken to verify the effect of Gangjihwan(Di-fatty, DF) composed with Pakistani Ephedra Herba on nonalcoholic fatty liver disease(NAFLD) using high fat diet-fed male mice. Method : Eight-week old C57BL/6N mice were used for all experiments. Standard chow diet-fed mice were used as normal group and high fat diet-fed NAFLD mice were randomly divided into 5 groups: control, atorvastatin, DF(1), DF(2) and DF(3). After 8 weeks, mice were treated with water, atorvastatin(10mg/kg) and DF(40, 80, 160mg/kg) for 8 weeks. And we investigated body weight gain, plasma lipid and glucose metabolism, histological analysis for liver on the mice. Results : Compared with controls, DF-treated mice had very significantly lower body weight gain and lower visceral adipose tissue weight, the magnitudes of which were prominent in DF(3). Consistent with their effects on body weight gain, DF-treated mice had lower blood total cholesterol and triglyceride level compared with controls. Consistent with their effects on body weight gain and blood plasma lipid level, DF-treated mice had lower liver weight and hepatic lipid accumulation of DF-treated groups was significantly decreased than control group. Also Blood plasma AST, ALT and γ-GT concentration were not changed by DF, and these results may indicate DF do not show any toxic effects. Conclusions : These results suggest that DF effectively improves NAFLD. DF reduces liver weight and prevents lipid accumulation of hepatocyte by reducing body weight gain and modulating blood plasma lipid metabolism levels.